O potrzebie demokratyzowania polskiej szkoły. Czas na krok następny – podmiotowość i współudział dzieci w edukacji - Jarosz, Ewa (Wydawnictwo Naukowe UAM, 2013)
The article joins the ongoing discourse on the democratisation processes in the school system, in particular in Polish schools. There is an urgent need to include in this discussion the question of the position of the child (pupil) among the different actors who impact the shape, content and process of education. The majority of this discourse addresses problems of the autonomy of particular schools to create education and of parents’ participation in school education. Children are a rare “topic” during considerations of problems and subjects of the democratisation of education and of school life. The article focuses on the empowerment of a child in school and its reality in Polish schools: in the school law and mostly in a school’s everyday life. It moreover considers this empowerment as mandatory in the concept of children’s participation and defines its core meaning.
On the Need of Democratisation of the Polish School System; Time for the Next Step – Empowerment and Participation of Children in Education
Keywords: education; children’s participation; democratisation of a school